TINJAUAN DAYA TAHAN ATLET JUDO PUTRA DI PEKANBARU - Wahyudi, Arief; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the observations that the author has made on male judo athletes in Pekanbaru during training and during competitions, the writer found outand encountered several problems, such as: when endurance training, some athletes got tired quickly when doing interval training of running for one hour, at 20-30 minutes the athletes were tired and asked to stop running and then walked and could not continue running until the time limit specified by the coach. Fatigue can also be seen when athletes did technical training (nage waza) for 1 minute, with 10 repetitionsand resting in every 10 seconds. From the exercise, the athletes were tired and theycould not finish the exercise until it finished.The purpose of this study was to determine how much endurance the male judo athletes in Pekanbaru. The sampling technique was the entire population (total sampling), amounting to 12 people. This type of research is descriptive research.Based on the results of the research, it can be concluded that the level of endurance of male judo athletes in Pekanbaru is in the “enough”category as many as 7 athletes namely 58.33%.Keywords: Endurance, Male Judo Athlete